The Welfare Effects of Mobile Broadband Internet : Evidence from Nigeria - Bahia, Kalvin; Castells, Pau; Cruz, Genaro; Masaki, Takaaki; Pedros, Xavier; Pfutze, Tobias; Rodriguez-Castelan, Carlos; Winkler, Hernan (World Bank, Washington, DC, 2020)
This paper estimates the impacts of mobile broadband coverage on household consumption and poverty in Nigeria, the largest economy and mobile broadband market in Africa. The analysis exploits a unique dataset that integrates three waves of a nationally representative longitudinal household survey on living standards with information from Nigerian mobile operators on the deployment of mobile broadband (3G and 4G) coverage between 2010 and 2016. The estimates show that mobile broadband coverage had large and positive impacts on household consumption levels which increased over time, although at a decreasing rate. Mobile broadband coverage also reduces the proportion of households below the poverty line, driven by higher food and non-food consumption in rural households. These effects are mainly due to an increase in labor force participation and employment, particularly among women.